Utilización del probiótico Lactobacillus bulgaricus en la alimentación de lechones en el periodo de lactancia para evitar afecciones gastrointestinales en el destete, en la cuidad de Tosagua, provincia de Manabí - Armendáriz Tapia, Diego José (2015)
To carry out this research plated the following objectives: Determine which of the levels studied probiotic Lactobacillus bulgaricus (1.5ml, 2.5ml, 3.5ml), is the most appropriate, determine the weight gain (g) in piglets treatment of Lactobacillus bulgaricus, set the morbidity - mortality in pigs study to determine the effectiveness of the implementation of the probiotic and assess the cost-benefit of using the productive efficiency of piglets. The research was conducted in the province of Manabí, Tosagua canton, San Francisco neighborhood in pig production owned by Mr. Cristobal Cevallos located 8 km northeast of the city of Tosagua. The methodology used was experimental where 34 piglets were used The duration of the investigation was a lapse of 35 days, the research involved four treatments that are T0: No application of probiotic Lactobacillus bulgaricus....